2011
DOI: 10.1007/s11192-010-0330-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge production through collaborative research in sub-Saharan Africa: how much do countries contribute to each other’s knowledge output and citation impact?

Abstract: This paper examines co-authorship of research articles in Thomson Reuters citation indexes in order to assess knowledge co-production in selected sub-Saharan African countries. Two indicators, namely publications and citations, were analysed to establish the patterns of knowledge co-production and its scientific impact, respectively. The study found that knowledge production through collaborative research among subSaharan African countries is minimal and contributes only a small percentage when compared to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
55
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 25 publications
8
55
0
1
Order By: Relevance
“…Some collaborative research exists between South Africa and Zimbabwe and South Africa and Namibia. These findings confirm those of Onyancha et al (2011) who identified that knowledge production through collaborative research among sub-Saharan African countries is minimal. Zimbabwe is the country collaborating most with SA among the SADC countries (almost 27% of all co-authored publications during the 2012-2014 period), followed by Tanzania and Malawi.…”
supporting
confidence: 89%
“…Some collaborative research exists between South Africa and Zimbabwe and South Africa and Namibia. These findings confirm those of Onyancha et al (2011) who identified that knowledge production through collaborative research among sub-Saharan African countries is minimal. Zimbabwe is the country collaborating most with SA among the SADC countries (almost 27% of all co-authored publications during the 2012-2014 period), followed by Tanzania and Malawi.…”
supporting
confidence: 89%
“…Sooryamoorthy (2009) investigated the collaboration patterns of South African researchers and Boshoff (2010) identified the collaborative patterns in the Southern African development community (SADC) countries. Onyancha and Maluleka (2011) found out that knowledge production through collaborative research among sub-Saharan African countries is minimal. Schubert and Sooryamoorthy (2010) showed that "a theory of scientific collaboration building on the notion of marginality and centre-periphery can explain many facets of South African-German collaboration, where South Africa is a semi-peripheral region, a centre for the periphery, and a periphery for the centre".…”
Section: Introductionmentioning
confidence: 99%
“…However, other scholars found that the research collaborations within African countries are still low, when compared with extra-Africa collaborations (Onyancha and Maluleka, 2011;Confraria and Godinho, 2015;Nature, 2015). Further, the research collaboration of the top publishing African countries is dominated by a few external partners, mainly the US, UK and France (Confraria and Godinho, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The level of collaborative research activities in Africa is substantially higher as compared to the rest of the world, although the intra-Africa collaboration is still low (Onyancha and Maluleka, 2011;Confraria and Godinho, 2015;Nature, 2015).…”
Section: Introductionmentioning
confidence: 99%